At home in nature : modern homesteading and spiritual practice in America - Gould, Rebecca Kneale, 1963- (University of California Press, 2005)
Motivated variously by the desire to reject consumerism, to live closer to the earth, to embrace voluntary simplicity, or to discover a more spiritual path, homesteaders have made the radical decision to go "back to the land," rejecting modern culture and amenities to live self-sufficiently and in harmony with nature